EXAMINING THE MEDIATING ROLE OF DIGITAL CULTURE ON DIGITAL TALENT IN THE TELECOMMUNICATION SECTOR - Khaira, Nurul; Triyonggo, Yunus; Sukmawati, Anggraini (Universitas Brawijaya, Indonesia, 2023)
The digital era is an era that cannot be avoided anymore. This era is characterized by the development of technology and the rapid flow of information. This digital transformation means that employees must have digital skills to adapt to the times. PT Telkom Indonesia Tbk (Telkom), the largest telkom company in Indonesia, also faces challenges in preparing digital talent that suits the company's needs in the future. One of these challenges is the existence of a talent war that results in each company having to be able to compete. The purpose of this study is to identify the characteristics of digital talent and analyze the influence of HR management, digital literacy, HR risk, digital leadership, and digital culture on PT Telkom Indonesia's digital talent. This study uses primary data obtained from 140 respondents of PT Telkom Indonesia employees from 14 work locations of digital talent employees. The method used in this research is Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis. The results of this study indicate that HR management, digital literacy, HR risk, digital leadership, and digital culture affect digital talent. Then, digital culture can mediate HR management, digital literacy, HR risk on digital talent. Meanwhile, digital culture does not successfully mediate digital leadership.Â The managerial implication of this research is that companies are expected to know the factors that form digital talent so that companies can prepare the right methods in managing digital talent.